2009
DOI: 10.1021/ef900234p
|View full text |Cite
|
Sign up to set email alerts
|

Study of HCl Absorption by CaO at High Temperature

Abstract: The reaction of CaO with HCl was investigated in a fixed-bed reactor fabricated of quartz glass at high temperatures (600−800 °C). The inlet HCl concentration was 2000 ppm. Two sorbents with mean particle sizes of 163 and 465 μm were obtained by calcination of CaCO3. The reaction rate constant was achieved by a deactivation model. The results show that sorbent S1 with small particle size has the higher reactivity and is insensitive to the reaction temperature. In this study, two sorbents have the highest capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 28 publications
1
38
0
1
Order By: Relevance
“…This concern originates with wet scrubber technology that has been widely used throughout industry. Some previous studies [2,[15][16][17] researching the chlorination of lime or limestone at elevated temperature have led to the conclusion that the maximum HCl capture capacity occurs approximately 650 ˚C and decreases rapidly as the temperature continues to rise. Chyang et al [17] suggested that the decrease of HCl capture capacity can be ascribed to the change of reaction equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…This concern originates with wet scrubber technology that has been widely used throughout industry. Some previous studies [2,[15][16][17] researching the chlorination of lime or limestone at elevated temperature have led to the conclusion that the maximum HCl capture capacity occurs approximately 650 ˚C and decreases rapidly as the temperature continues to rise. Chyang et al [17] suggested that the decrease of HCl capture capacity can be ascribed to the change of reaction equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…With these constraints it has been proposed that HCl concentrations not exceed 1 mg m −3 [60]. However, MSW can contain large amounts of chlorine and, during its conversion into energy, HCl might simply be emitted together with other impurities such as SO 2 and NO x [61,62]. In terms of overall design outside of fuel cell applications, their presence in the reaction system has a negative impact on process equipment and plant effectiveness due to downtime associated with cleaning.…”
Section: Catalyst and Sorbents Screening For Chlorine Removal And Othmentioning
confidence: 99%
“…It was also shown that chlorine contamination can be removed by calcium-based sorbents in a fluidized bed or via filtration accumulating in the filter cake which reduced the need for sorbent injection, but chlorine removal increased to 60% when slaked lime was added to the product gas line [70]. Moreover, it was reported that a CaO sorbent with small particle size (163 µm) has higher reactivity and greater chlorine capacity than the same sorbent with a mean particle size of 465 µm [62]. Both sorbents were able to reduce the initial HCl concentration (2000 ppm) to less than 40 ppm.…”
Section: Catalyst and Sorbents Screening For Chlorine Removal And Othmentioning
confidence: 99%
“…그러나 상기 고체 입자들의 비용 은 비교적 고가이며, 따라서 저렴한 비용으로 생산 가능한 입 자 개발이 요구되고 있다 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. 현재까지 가장 잘 알려진 HCl 제거 공정은 CaO, Ca(OH)2 등을 이용하는 방법이며, 이때의 운전온도는 500 ℃ 이하이다 [2][3][4].…”
Section: 서 론unclassified